Pengaruh Variabel Macroeconomic terhadap Firm Performance pada Sektor LQ45 - Yandi Suprapto; Junita Junita (Universitas Jember, 2023)
Two years aftar the global recession due to the pandemic caused by COVID-19, fears of a global recession have emerged due to the return of inflation triggered by the increase in interest rate by central banks in several countries, including Indonesia. This research is conducted to examine macroeconomic indicators’ effect, namely gross domestic product, inflation, exchange rate, interest rate and unemployment rate on firm performance. This study used 28 companies listed in the LQ45 sector during 2017-2021 consecutively. Panel regression method is chosen as the method of this research as panel data is analyzed. The results of the study show that the variables such as gorss domestic product, inflation, interest rate, unemployment rate have a significant effect, while the exchange rate variable does not have a significant effect on firm performance Keywords: Gross domestic product, Inflation, Exchange rate, Interest rate, Unemployment rate